Relevance of Ramayana in our Daily Lives in the Context of the Present Situation (British Journal of Multidisciplinary and Advanced Studies, 2024)
Rishi Valmiki was the first to forge the grand form of Itihasa and to create a unique prosodic pattern for the epic literary genre of the Ramayana. As time goes on, people experience stress, frustration, mental and physical illnesses, a lack of brotherhood, a lack of religious practice, a lack of love for the natural world and its creatures, and a lack of moral and ethical principles. Objectives: The study aims to determine how applicable the Ramayana is to modern society and how it affects our daily lives. Methods: This study has taken a qualitative approach and is descriptive, drawing on secondary data for its design. Results and Discussion: Several key takeaways from the Ramayana are examined, including how Dharma affects our lives. People acquire skills such as accountability, social duty, authenticity, and other related ones. Findings: The computerised lives of people in the modern era can be drastically changed by the timeless relevance of ancient epics such as the Mahabharata and the Ramayana. Conclusion: In actuality, the Ramayana offers insightful lessons that we can apply to to our day-to-day existence without any complicity. All situations—individual, familial, and broader aspects of social and professional ambiguities—can benefit from these solutions.